PENYULUHAN EKONOMI KREATIF BAGI PERUBAHAN SOSIAL EKONOMI MASYARAKAT MUARA TAKUS BATAM - Purba, Gomgom,; Pasaribu, George Rudi Hartono; Sitohang, Dino Tridiyanika; Hutabarat, Jessica Janet (JURNAL BEATITUDES, 2024)
Abstract The aim of this research is to find out about creative economy counseling for socio-economic changes in the Muara Takus Batam community to map economic opportunities from the creative industry which is part of the creative economy as well as employment opportunities. This research is research in the form of field research or field research is a type of research. This research is a qualitative descriptive research. The data in this research comes from primary and secondary data. Data collection methods use observation, interviews and documentation. Interviews were conducted with the community at the PkM location. Data analysis in this research uses the Miles and Huberman model which suggests that there are three activities in qualitative research, namely reduction, data display and conclusion drawing or verification. The research results obtained in the implementation of community empowerment through the creative economy development program in Kampung Seraya where the stages of community empowerment outreach in developing the creative economy are not optimal in accordance with the goals to be achieved, problems in empowerment are not yet optimal, such as the lack of knowledge possessed by human resources. creative economy, quality production and innovation and can have good selling value in the marketing process. There is a lack of awareness among community members, especially those who manage the creative economy, to take part in programs implemented by the Batam city government in training and empowering the creative economy. The inhibiting factor in community empowerment efforts lies in the community itself because participation is still very lacking so that maximizing existing human resources is less than optimal. Key words: Creative economy, social, Muara Takus, Batam